THE POSSIBILITIES OF APPLICATION OF ONLINE SERVICES IN THE HIGHER EDUCATIONAL SYSTEM - Khamrokhujaeva S.T.; Scientific Adviser: Davirova Sh.Sh. (Galaxy International Interdisciplinary Research Journal, 2023)
The transformation of teaching methods, caused by changes in the lifestyle of the young generation in a rapidly developing world, leads to the need of choosing the most effective services for the implementation of the educational process by teachers based on the personal capabilities and needs of the modern world. This article examines the main characteristics and possibilities of using the most popular online educational platforms today (like Padlet, Mentimeter, Kahoot, Online Test Pad and QuizBot) in economic universities. Here their description and qualities are presented in terms of the practicality of their application for organizing interactive work with student teachers. The authors of the work propose ways to introduce online tools in the process of teaching economic disciplines and assessing the assimilation of materials by students, as well as stimulating their independent activity. Along with this, judgments are made about the rationality of using some of the capabilities of the presented interactive educational platforms and proposals on the prospects for improving the quality of pedagogical activity in this area.